An 8‐week, open‐label, dose‐finding study of nimodipine for the treatment of progranulin insufficiency from GRN gene mutations. Issue 4 (30th August 2017) - Sha, Sharon J.; Miller, Zachary A.; Min, Sang‐won; Zhou, Yungui; Brown, Jesse; Mitic, Laura L.; Karydas, Anna; Koestler, Mary; Tsai, Richard; Corbetta‐Rastelli, Chiara; Lin, Sophie; Hare, Emma; et al.
Abstract: Introduction: Frontotemporal lobar degeneration–causing mutations in the progranulin ( GRN ) gene reduce progranulin protein (PGRN) levels, suggesting that restoring PGRN in mutation carriers may be therapeutic. Nimodipine, a Food and Drug Administration–approved blood‐brain barrier‐penetrant calcium channel blocker, increased PGRN levels in PGRN‐deficient murine models. We sought to assess safety and tolerability of oral nimodipine in human GRN mutation carriers. Methods: We performed an open‐label, 8‐week, dose‐finding, phase 1 clinical trial in eight GRN mutation carriers to assess the safety and tolerability of nimodipine and assayed fluid and radiologic markers to investigate therapeutic endpoints. Results: There were no serious adverse events; however, PGRN concentrations (cerebrospinal fluid and plasma) did not change significantly following treatment (percent changes of −5.2 ± 10.9% in plasma and −10.2 ± 7.8% in cerebrospinal fluid). Measurable atrophy within the left middle frontal gyrus was observed over an 8‐week period. Discussion: While well tolerated, nimodipine treatment did not alter PGRN concentrations or secondary outcomes.